Mental Health Stigma and Barriers to Accessing Psychological Services in Urban Communities - Kori Puspita Ningsih; Seno Lamsir (PT. Anagata Sembagi Education, 2025)
Mental health stigma remains a major obstacle to accessing psychological services in urban communities. This study employs a Systematic Literature Review guided by PRISMA to examine public stigma, self stigma, structural barriers, and digital factors influencing help seeking behaviors. Out of 684 identified publications, 62 articles met the criteria and were thematically synthesized. The findings indicate that stigma is reinforced by cultural norms, social expectations, and gaps in mental health literacy. Economic barriers, limited workforce distribution, and fragmented service systems further restrict access. While digital mental health platforms offer new opportunities, digital inequalities and privacy concerns reduce adoption among vulnerable groups. The study highlights that reducing stigma and improving access require multidimensional approaches involving policy reform, community based interventions, mental health education, and safe, inclusive digital solutions. These findings provide an evidence based foundation for designing systemic interventions to strengthen urban mental health ecosystems in Indonesia